(untitled) (Research, Society and Development, 2023)
A sizable portion of nations’ populations nowadays are multicultural, according to current statistics. The design of therapy materials, practice models, evaluation tools, and client collaboration are all thought to be greatly influenced by culture. Also, current writings discuss the significance of comprehending a child’s needs in light of the prevailing society as well as the relationship between a therapist and a client. Ethnic minority youths and teens still trail behind their non-minority peers in terms of diagnosis and treatment rates, despite major improvements in the creation and implementation of effective services for kids with ADHD. This study aims to analyze the literature on factors predicting treatment for children from ethnic minorities who have ADHD and the efficacy of employing mobile apps to recognize and treat the disorder’s symptoms. The prognostic factors that affect how minority children with ADHD are treated are the focus of this literature review, which tries to address the issue. Last but not least, it is discussed how approaches, assessments, and interventions need to be modified to account for minority children’s use of mobile devices and, in particular, physical activity.